ANALYSIS OF SECURITY MANAGEMENT ACTIVITIES AND ECONOMIC CONSEQUENCES OF CORRUPTION IN PRIVATIZATION OF AGRICULTURAL LAND IN SERBIA - Đukić, Stanimir; Avramović, Nenad (Economics of Agriculture, 2021)
Security management does not make strategic decisions, but it significantly influences their decision-making by providing top management with information and assessments on the basis of which strategic goals are defined and operational decisions are made. The paper also discusses the economic consequences of corruption in the privatization of agricultural land. The subject of the paper is privatization - a litmus test that clearly shows the strength of the Governments commitment to implement comprehensive reforms, primarily due to the consequences it causes in terms of social status and, more importantly, cultural patterns and way of thinking of the population. With privatization, the new owners would very often launder the money gained from criminal activities or would be interested only in acquiring attractive real estate, but not in preserving the production program, which led to a large number of fired workers and destroyed companies.